1997
DOI: 10.1002/(sici)1097-0185(199710)249:2<276::aid-ar15>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Human facial muscles: Dimensions, motor endplate distribution, and presence of muscle fibers with multiple motor endplates

Abstract: Background: Extrafusal muscle fibers of human striated skeletal muscles are known to have a uniform innervation pattern. Motor endplates (MEP) of the ''en plaque'' type are located near the center of muscle fibers and distributed within the muscles in a narrow band. The aim of this study was to evaluate the innervation pattern of human facial muscles and compare it with that of skeletal muscles.Methods: Ten facial muscles from 11 human cadavers were dissected, the nerve entrance points located, and the dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 33 publications
5
56
0
6
Order By: Relevance
“…8 An increased number of sodium channels in facial muscles compared with other skeletal muscles may explain the findings associated with SCN4A mutations. 8,17,18 Consistent with our analysis, the only other genetic study performed on patients with strabismus in addition to myotonia also found the V445M mutation. 19 There may be an association between this mutation and extraocular muscles.…”
Section: Discussionsupporting
confidence: 90%
“…8 An increased number of sodium channels in facial muscles compared with other skeletal muscles may explain the findings associated with SCN4A mutations. 8,17,18 Consistent with our analysis, the only other genetic study performed on patients with strabismus in addition to myotonia also found the V445M mutation. 19 There may be an association between this mutation and extraocular muscles.…”
Section: Discussionsupporting
confidence: 90%
“…Each facial muscle is made up out of 75-150 muscle fibres (Rubin, 1999). They are arranged into parallel bundles, which run from origin to insertion (Happak et al, 1997).…”
Section: Facial Muscle Characteristicsmentioning
confidence: 99%
“…The human face contains 23 paired facial muscles and 1 unpaired, the orbicularis oris, which are all unique from other skeletal muscles in that they attach at least one side to the skin, making facial expression possible through this skin movement [38]. Each facial muscle consists of 75-150 muscle fibers [39] arranged in parallel bundles running from origin to insertion [40] and allowing for Type I (slow twitch) and Type II (fast twitch) muscle fibers to be distinguished as well [41]. Slow twitch muscle fibers are able to work for a long time without getting exhausted due to their ability to produce large amounts of energy at a slow pace.…”
Section: Facial Muscle Characteristicsmentioning
confidence: 99%